Symptom burden and quality of life in cam and non-cam users among breast cancer patients during chemotherapy / Chui Ping Lei - Chui, Ping Lei (2015)

(untitled)
Patients often use complementary and alternative medicine (CAM) to manage their side-effects and symptoms as well as to enhance their quality of life (QOL), although little empirical data exists to support CAM use. The objective of this study was to assess the pattern of CAM use among breast cancer patients undergoing chemotherapy and to examine its association with symptom burden and QOL. A cross-sectional study was conducted at two outpatient chemotherapy centres. A total of 546 patients completed the questionnaire on their usage of three categories of CAM: mind-body practices (MBPs), natural products (NPs) and traditional medicine (TM). Symptom burden was measured using the Side Effect Burden Scale. QOL was evaluated based on the EORTC QLQ-C30 and EORTC QLQ-BR23 questionnaires. A total of 70.7% (n = 386) reported using some form of CAM, while 29.3% (n = 160) were non-CAM users. The odds of CAM use among patients who postponed their chemotherapy schedule was 5.71 times higher compared to patients who adhered to their chemotherapy schedule. The odds for CAM use among patients with average monthly household incomes above RM 3000 was 3.41 times higher compared to patients whose monthly household income was RM 3000 or below. The odds of CAM use among patients with tertiary education was 2.31 times higher compared to patients with primary or lower educational levels. The odds of CAM use among patients with advanced stage breast cancer was 1.86 times higher compared to patients with early stage breast cancer. The main reason for using MBPs, NPs and TM was to improve emotional well-being (92.0%), recommendation by others (70.4%) and to assist in treating cancer (84.6%) respectively. A total of 26% of the NPs users and 40% of the TM users reported using NPs and TM to cure their cancer. The most popular CAM modality was MBP (n=342), followed by NP (n=299), and TM (n=129). There were no significant differences in the total symptom burden score between CAM users (40.39± 2.61) and non-CAM users (36.93±3.21). Among CAM users, MBP-NP-TM users (47.44±4.12) reported significantly higher total symptom burden scores than MBPs users (34.09±4.43). The odds of having high total symptom burden among the MBP-NP-TM users were 12.9 times higher compared to MBP users. There was no significant difference in overall QOL between CAM users (62.95 ±2.38) and non-CAM users (64.52±2.94), and among MBP (60.17±4.10), MBP-NP (63.80±3.04) and MBP-NP-TM (64.83±3.82) users. The odds of having high global health status scores among patients with low total symptom burden scores was 28.89 times higher compared to patients with high total symptom burden scores. The use of CAM-modality was not significantly associated with high global health status scores (p=0.71). CAM use was common among breast cancer patients and made no difference on patients’ total symptoms burden and QOL. MBP use was associated with lower total symptom burden and this was in turn associated with high QOL. MBP usage was however not associated with high QOL. An open discussion with breast cancer patients using CAM during chemotherapy is essential.